ANXIOUS-PREOCCUPIED ATTACHMENT TO FATHER: DOES PERMISSIVE PARENTING CONTRIBUTED? - Fatmawati, Fatmawati; Maryam, Siti (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
In fact, parents nowadays tend to liberate their children more in everything. That is because parents –especially fathers, spend more time working, so in the end children get less attention. These actions that the parent takes are related to the use of permissive parenting. Children with low attention level (permissive parenting) from their fathers are predicting to have an insecure attachment, including anxious-preoccupied attachment. To that end, this study aimed to investigate the relationship between permissive parenting and anxious-preoccupied attachment to fathers among adolescents in Pidie-Aceh, Indonesia. This study used a purposive sampling technique with a total sample of 200 teenagers. Data collection techniques were performed by using permissive parenting scale and anxious-preoccupied attachment to father scale. The Pearson correlation test results showed that permissive parenting was positively related to anxious-preoccupied attachment to fathers (r count = 0.122; p = 0.042). The analysis proved that permissive parenting was significantly related to adolescents’ attachment to their fathers.